Three-dimensional dynamics of thin liquid films on vertical cylinders with Marangoni effect - Ding, Zijing (2017)
The effects of thermocapillary force on the three dimensional dynamics of thin liquid films flowing down a uniformly heated vertical cylinder are investigated using a thin film model. Linear and nonlinear analyses predict the existence of a non-axisymmetric mode due to the Marangoni effect. Symmetry-breaking of axisymmetric steady traveling waves is observed when the Marangoni number exceeds a critical value. Linear stability analysis demonstrates that the steady traveling wave can be unstable to azimuthal disturbances due to the Marangoni effect, leading to the formation of non-axisymmetric patterns.